2004
DOI: 10.1007/s10269-005-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Iodine 131 in the treatment of well differentiated carcinoma of the thyroid metastases

Abstract: or bone metastases proves to be more favourable than the vesicular type (63.75 versus 25%). The analgesic effect was spectacular on painful bone metastases. These results are discussed in light of recent data of molecular and radiobiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Our results are almost identical to those of Biyi A D et al [39] (22), who noted a strong axial predominance in 80% of cases. The study by Paycha et al [7] Open Journal of Medical Imaging found metastases in the dorsolumbar spine in 50%, the costal gril in 20%, the pelvic girdle in 15% and the sternum in 10%.…”
Section: -Contribution Of Bone Scintigraphysupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are almost identical to those of Biyi A D et al [39] (22), who noted a strong axial predominance in 80% of cases. The study by Paycha et al [7] Open Journal of Medical Imaging found metastases in the dorsolumbar spine in 50%, the costal gril in 20%, the pelvic girdle in 15% and the sternum in 10%.…”
Section: -Contribution Of Bone Scintigraphysupporting
confidence: 92%
“…The study by Biyi A. D. [39] reported that the dorsal spine and costal grill were the sites most affected by bone metastases.…”
Section: -Contribution Of Bone Scintigraphymentioning
confidence: 99%